A mixed-methods pilot study to evaluate a collaborative anaesthetic and surgical training package for emergency surgical cricothyroidotomy. Issue 4 (July 2019) - Berwick, Richard J; Gauntlett, William; Silverio, Sergio A; Wallace, Hilary; Mercer, Simon; Brown, Jeremy M; Sandars, John E; Morton, Ben; Groom, Peter
In a 'can't intubate, can't oxygenate' scenario, success of emergency front-of-neck access is dependent upon a clinician's skill, competence and confidence to initiate the procedure. Surgical cricothyroidotomy is an important airway skill, as it can be employed as both the primary method of emergency front-of-neck access or as a rescue approach if a needle technique should fail. We designed a collaborative surgical and anaesthetic training package to address perceived anaesthetic reluctance to perform surgical cricothyroidotomy and undertook a pilot study of the package using a mixed-methods approach. The package consisted of three elements: theory teaching, surgical experience and repeated high-fidelity simulation. Ten anaesthetic trainees were trained using the package. Training comprised face-to-face tuition on the 2015 Difficult Airway Society guidelines, the Vortex cognitive aid, manikin-based surgical cricothyroidotomy instruction and surgical experience gained from an elective surgical tracheostomy. A standardised, high-fidelity in situ 'can't intubate, can't oxygenate' simulation was used to assess performance at baseline and at two weeks and six months after training. Participants scored their self-efficacy, underwent qualitative semi-structured interviews and had their performance quantitatively assessed to evaluate this training. Six months following training, participants' performance had improved. They reported significantly increased self-efficacy and demonstrated significantly reduced deliberation time to initiate surgical cricothyroidotomy in the simulated 'can't intubate, can't oxygenate' emergency. Thematic framework analysis of interview transcripts revealed that reluctance to perform surgical cricothyroidotomy was related to fear and anxiety in regard to performing the procedure. These results support wider adoption of collaborative educational training packages, including hands-on surgical teaching, to improve trainees' efficacy and confidence with surgical cricothyroidotomy and front-of-neck access in an emergency 'can't intubate, can't oxygenate' scenario.